Identification of epitopes recognised by mucosal CD4+ T-cell populations from cattle experimentally colonised with Escherichia coli O157:H7. (December 2016) - Corbishley, Alexander; Connelley, Timothy; Wolfson, Eliza; Ballingall, Keith; Beckett, Amy; Gally, David; McNeilly, Tom
Abstract Vaccines targeting enterohaemorrhagicEscherichia coli (EHEC) O157:H7 shedding in cattle are only partially protective. The correlates of protection of these vaccines are unknown, but it is probable that they reduce bacterial adherence at the mucosal surface via the induction of blocking antibodies. Recent studies have indicated a role for cellular immunity in cattle during colonisation, providing an impetus to understand the bacterial epitopes recognised during this response. This study mapped the epitopes of 16 EHEC O157:H7 proteins recognised by rectal lymph node CD4+ T-cells from calves colonised with Shiga toxin producing EHEC O157:H7 strains. 20 CD4+ T-cell epitopes specific toE. coli from 7 of the proteins were identified. The highly conserved N-terminal region of Intimin, including the signal peptide, was consistently recognised by mucosal CD4+ T-cell populations from multiple animals of different major histocompatibility complex class II haplotypes. These T-cell epitopes are missing from many Intimin constructs used in published vaccine trials, but are relatively conserved across a range of EHEC serotypes, offering the potential to develop cross protective vaccines. Antibodies recognising H7 flagellin have been consistently identified in colonised calves; however CD4+ T-cell epitopes from H7 flagellin were not identified in this study, suggesting that H7 flagellin may act as a T-cell independent antigen. This is the first time that the epitopes recognised by CD4+ T-cells following colonisation with an attaching and effacing pathogen have been characterised in any species. The findings have implications for the design of antigens used in the next generation of EHEC O157:H7 vaccines.